1996
DOI: 10.1524/ract.1996.72.3.137
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Subgroup IV, V and VI Elements on Ion Exchangers from HCl/HF Solutions. Model Experiments for Chemical Studies of the Elements 105 and 106 in Aqueous Solution

Abstract: The distribution coefficients of Zr, Hf, Nb, Ta, Mo, W, and Pa on cation and anion exchange resins from mixed HCl/HF solutions were determined in batch experiments by radiometric measurements. From solutions of 0.05 to 0.1 M HCl with 1.0 X10"' M HF a Separation of subgroup V and VI from subgroup IV Clements is possible on DOWEX 50X8. This system is proposed for the fast on-line Separation of the Clements 105 and 106. In column experiments with cation exchangers W can be separated from Mo. This opens the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 10 publications
3
20
1
Order By: Relevance
“…Predictions of the sorption properties of elements in ultra trace amounts are difficult because the tracers may behave very different than macroscopic amounts under identical conditions. Speciation calculations using literature data for zirconium hydrolysis [11] and fluoride complexation [12] showed that ZrFl^ and ZrF^ are the main species in 0.05-0.1 M HCl/lO-'^-lO-^ M HF Solution [13], According to this speciation, the subgroup IV elements zirconium and hafnium should sorb on cation exchange resins, which we could recently confirm experimentally [1].…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…Predictions of the sorption properties of elements in ultra trace amounts are difficult because the tracers may behave very different than macroscopic amounts under identical conditions. Speciation calculations using literature data for zirconium hydrolysis [11] and fluoride complexation [12] showed that ZrFl^ and ZrF^ are the main species in 0.05-0.1 M HCl/lO-'^-lO-^ M HF Solution [13], According to this speciation, the subgroup IV elements zirconium and hafnium should sorb on cation exchange resins, which we could recently confirm experimentally [1].…”
Section: Resultssupporting
confidence: 52%
“…The suitable concentration interval of 0.05-0.1 M HCl/10-''-10'M HF for the Separation of subgroup VI from subgroup IV elements on cation exchange resins was developed using molybdenum and tungsten, zirconium and hafnium, respectively, as model elements [1]. Predictions of the sorption properties of elements in ultra trace amounts are difficult because the tracers may behave very different than macroscopic amounts under identical conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations